Sri Lanka : First Review Under the Stand-By Arrangement; Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Sri Lanka. (IMF Staff Country Reports; Country Report ;, 2010)
Sri Lanka' performance under the Stand-by Arrangement is encouraging, but fundamental vulnerabilities remain. Executive Directors emphasized the need for strict adherence to program targets and steadfast implementation of the reform agenda. They commended deficit reduction and planned fiscal reforms through expenditure restraint and tax reform for simplifying the system. They appreciated the improvement in financial sector reform brought about by improving the bank resolution framework. They emphasized that post-war reconstruction needs should be met by diverting budget resources from military activities, as well as through donor financing.